Comparing the impact of future cropland expansion on global biodiversity and carbon storage across models and scenarios. (16th March 2020) - Molotoks, Amy; Henry, Roslyn; Stehfest, Elke; Doelman, Jonathan; Havlik, Petr; Krisztin, Tamás; Alexander, Peter; Dawson, Terence P.; Smith, Pete
Abstract : Land-use change is a direct driver of biodiversity and carbon storage loss. Projections of future land use often include notable expansion of cropland areas in response to changes in climate and food demand, although there are large uncertainties in results between models and scenarios. This study examines these uncertainties by comparing three different socio-economic scenarios (SSP1–3) across three models (IMAGE, GLOBIOM and PLUMv2). It assesses the impacts on biodiversity metrics and direct carbon loss from biomass and soil as a direct consequence of cropland expansion. Results show substantial variation between models and scenarios, with little overlap across all nine projections. Although SSP1 projects the least impact, there are still significant impacts projected. IMAGE and GLOBIOM project the greatest impact across carbon storage and biodiversity metrics due to both extent and location of cropland expansion. Furthermore, for all the biodiversity and carbon metrics used, there is a greater proportion of variance explained by the model used. This demonstrates the importance of improving the accuracy of land-based models. Incorporating effects of land-use change in biodiversity impact assessments would also help better prioritize future protection of biodiverse and carbon-rich areas. This article is part of the theme issue 'Climate change and ecosystems: threats, opportunities and solutions'.